Theory and applications of satisfiability testing - SAT 2011 14th international conference, SAT 2011, Ann Arbor, MI, USA, June 19-22, 2011. Proceedings - Sakallah, Karem A.; Simon, Laurent (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 14th International Conference on Theory and Applications of Satisfiability Testing, SAT 2011, held in Ann Arbor, MI, USA in June 2011. The 25 revised full papers presented together with abstracts of 2 invited talks and 10 poster papers were carefully reviewed and selected from 57 submissions. The papers are organized in topical sections on complexity analysis, binary decision diagrams, theoretical analysis, extraction of minimal unsatisfiable subsets, SAT algorithms, quantified Boolean formulae, model enumeration and local search, and empirical evaluation.